The Measurement of Orthopaedic Surgeon Burnout Using a Validated Wearable Device - Kyle R. Sochacki, M.D; David Dong, B.S; Leif Peterson, Ph.D; Patrick C. McCulloch, M.D; Joshua D. Harris, M.D (Elsevier, 2019)
Purpose: The purpose of this study was (1) to determine the prevalence of burnout in orthopaedic surgeons and (2) to determine whether there is an association or correlation between subject-specific variables (age, attending physician, resident, postgraduate year level, gender, number of calls, total hours worked, and total hours of sleep) and burnout. Methods: Surgeons were prospectively enrolled and provided with a validated wearable device. Subject-specific variables were recorded. Participants completed the Maslach Burnout Inventory and Patient-Reported Outcomes Measurement Information System (PROMIS-29) weekly. Burnout and burnout risk were defined. Multivariate analysis and bivariate correlations were used to determine the association and correlation between subject-specific variables and burnout. Residents were compared to attending surgeons. Results: Of the 26 enrolled subjects, 21 (15 males, 6 females; mean age 37.2 ± 10.9) completed the 4-week study. Residents worked significantly more hours per week than attending surgeons (68.5 ± 15.2 versus 49.9 ± 7.5, P = 0.009). Of the orthopaedic surgeons, 6 (28.6%) experienced burnout, and 7 (33.3%) orthopaedic surgeons were at risk for burnout. There was no significant difference in burnout rates between residents and attending surgeons (P > 0.05). The number of overnight calls was significantly correlated with increased burnout (r = 0.435, P = 0.049). Female gender was significantly associated (P = 0.041) and correlated (r = 0.558, P = 0.009) with burnout. There was no significant association with burnout between the number of hours worked and hours of sleep. Conclusions: The rate of burnout was less than 50% among orthopaedic surgeons. The number of overnight calls and female gender are significantly correlated with increased burnout. There was no significant correlation between hours worked and hours of sleep in surgeon burnout. Clinical Relevance: Burnout is an increasingly common problem among orthopaedic surgeons, and it can have significant negative effects on surgeons' health and patients' outcomes. Identifying the predictors of burnout would allow surgeons to address these risk factors and reduce burnout.